TAFSIR AYAT AHKÂM GENDER (Kajian tentang Bagian Hak Waris dan Kepemimpinan Perempuan) - Neni Nuraeni (Asy-Syari'ah, 2014)
At the centuries ago, the tradition of the inheritance distribution was main provisions by their ancestors in which the children and women are prohibited from getting the inheritance. Even, a widow is part of the inheritance that allowed to be inherited and contributed themselves. This situation continued until Islam came and freed women from a variety of oppression. However, this did not completely solve the problem of differences between the rights of men and women. It means there are still some verses being debated, for example the verse which explains the distribution of inheritance and leadership. This paper attempts to discuss issues related to these two issues that are the inheritance and leadership